Diskursus Hakikat Kurikulum Pendidikan Islam - Samad, Sri Astuti A. (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2021)
This study discusses the nature of the curriculum in Islamic education which is an important component in education. This paper is qualitative in nature with an Islamic educational philosophy approach. The research concludes that the basic framework of the Islamic education curriculum is based on revelation and value of tauhid to Allah SWT. The curriculum has four foundations, namely; philosophical, sociological, organizational, and psychological, while the principles of the curriculum, for example, are based on Islamic values, integral and flexible. Then the first curriculum orientation is preserved Islamic values, students, labor and science and technology. In essence, the curriculum content must include three parts, namely; scientific intelligence (cognitive), skills (psychomotor) and values. Likewise the curve of evaluation and review as changes from social change and the times. Therefore, it is important to emphasize that essence, basic framework, principles, orientation and content refer to the reference to Islamic values ​​and monotheism as a characteristic and relationship of Islamic education. This characteristic of monotheism is what distinguishes Islamic education and Western education from a philosophical perspective.